2010
DOI: 10.1242/dev.055293
|View full text |Cite
|
Sign up to set email alerts
|

SPAT-1/Bora acts with Polo-like kinase 1 to regulate PAR polarity and cell cycle progression

Abstract: During asymmetric cell division, cell polarity and cell cycle progression are tightly coordinated, yet mechanisms controlling both these events are poorly understood. Here we show that the Bora homologue SPAT-1 regulates both PAR polarity and cell cycle progression in C. elegans embryos. We find that, similarly to mammalian cells, SPAT-1 acts with PLK-1 and not with the mitotic kinase Aurora A (AIR-1), as shown in Drosophila. SPAT-1 binds to PLK-1, and depletion of SPAT-1 or PLK-1 leads to similar cell divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 42 publications
10
68
0
Order By: Relevance
“…Phosphorylated (p)Bora accumulates at the G2-M transition and pBora/pSPAT-1 co-precipitate with Plk1/PLK-1, both in human cells 19,27 and in C. elegans embryos, 30 suggesting that the interaction between Bora/SPAT-1 and Plk1/PLK-1 might be regulated by phosphorylation. However, Seki et al showed that the phospho-Bora/Plk1 complex is resistant to lambda phosphatase treatment indicating that Bora phosphorylation is dispensable for the interaction between Bora and Plk1, or at least, not required to maintain this interaction.…”
Section: How Is the Interaction Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylated (p)Bora accumulates at the G2-M transition and pBora/pSPAT-1 co-precipitate with Plk1/PLK-1, both in human cells 19,27 and in C. elegans embryos, 30 suggesting that the interaction between Bora/SPAT-1 and Plk1/PLK-1 might be regulated by phosphorylation. However, Seki et al showed that the phospho-Bora/Plk1 complex is resistant to lambda phosphatase treatment indicating that Bora phosphorylation is dispensable for the interaction between Bora and Plk1, or at least, not required to maintain this interaction.…”
Section: How Is the Interaction Betweenmentioning
confidence: 99%
“…Phenotypic and biochemical analysis revealed that AIR-1 either is not the activating kinase or not the only one. 30,31 Therefore, one possibility is that non-modified SPAT-1 might be able to activate PLK-1, similarly to Bora, but AIR-1 is not the physiological kinase and this prevents the detection of this activation in our in vitro assays. Alternatively SPAT-1 might be more dependent than Bora on Cdk1 phosphorylation to interact with and activate PLK-1.…”
Section: How Is the Interaction Betweenmentioning
confidence: 99%
“…The linker domain, which is phosphorylated by Aurora A, would also provide coordination between cell cycle progression and spindle positioning [59]. In C. elegans embryos, downregulation of the Aurora A homolog, AIR-1, causes cell polarity defects [60,61]. PAR-2, normally found at the posterior of one-cell embryos, is found at both poles in air-1(RNAi) embryos, whereas PAR-6 is found in a central band [60].…”
Section: Trends In Cell Biologymentioning
confidence: 99%
“…In C. elegans embryos, downregulation of the Aurora A homolog, AIR-1, causes cell polarity defects [60,61]. PAR-2, normally found at the posterior of one-cell embryos, is found at both poles in air-1(RNAi) embryos, whereas PAR-6 is found in a central band [60]. It is not known whether AIR-1 phosphorylates PAR-6 or any other PAR protein in C. elegans.…”
Section: Trends In Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation